The penguin dictionary of english synonyms and antonyms - Fergusson, Rosalind (Penguin London, 1992)
This is the latest edition of a classic English language reference book that gives synonyms for a huge range of key headwords. Antonyms are also listed where applicable for verbs, nouns and adjectives